Shoot Blight Caused by Sirococcus tsugae on Eastern Hemlock (Tsuga canadensis) in Georgia - Stanosz, G R (Plant disease, 2011)
Eastern hemlock (Tsuga canadensis) is an ecologically and economically important conifer from the north-central United States to the east coast of North America to the southern Appalachian Mountains. In early spring 2010, blighted shoot tips of eastern hemlock were observed at widely separated locations in the Chattahoochee National Forest in north Georgia. Damage did not appear to be directly related to hemlock woolly adelgid (Adelges tsugae) activity, which was sporadic or absent in some areas where symptoms were observed. A preliminary survey in March 2010 revealed that incidence of blighted shoots on individual trees varied, but was as high as 70%. Stems of shoots produced the previous year were frequently necrotic, had lost needles, and bore pycnidia with hyaline, two-celled conidia consistent with those of Sirococcus tsugae (2,3). Later in the spring and summer, shoots of the current year's growth became blighted, with sporulation of S. tsugae also on dead and dying needles. While S. tsugae previously has been reported on T. heterophylla, T. mertensiana, Cedrus atlantica, and C. deodara in western North America, it has only recently been reported on eastern hemlock (1), and its ability to induce shoot blight has not been proven. Pure cultures (2,3) were obtained on streptomycin-amended potato dextrose agar (PDA) and their identity was confirmed by species-specific PCR primers (4). Nuclear rDNA internal transcribed spacer sequence (554 nucleotides) also was obtained for isolate 10-05 and deposited in GenBank (Accession No. HQ256769). This sequence was found to be identical to sequences previously deposited for S. tsugae isolates. Isolate 10-05 and a second isolate (10-06) were used to inoculate potted 2-year-old eastern hemlock seedlings in a growth chamber at 20°C with a 16-h photoperiod. Conidia were collected by flooding 1-month-old colonies on PDA with sterile water. Expanding shoots on one branch of each seedling were wounded using scissors to cut the tips off needles and stems, while another branch remained nonwounded. Ten seedlings per isolate were inoculated by spraying to runoff with a suspension of 5 × 106 conidia ml-1 in sterile water, and five similarly treated control seedlings were sprayed with sterile water. Seedlings were covered with plastic bags to maintain high humidity for 4 days. Germination of conidia of each isolate incubated on water agar in this growth chamber was >80% after 24 h. Symptoms were evaluated and reisolation was attempted on streptomycin-amended PDA 2 months after inoculation. Symptoms of seedlings inoculated with either isolate included chlorotic and necrotic needle spots, browning of cut edges of needles, browning and death of needle tips and entire needles, death of stem tips with retention of dead needles, and needle loss. Symptoms of control seedlings were limited to slight browning of cut edges of needles. The fungus was reisolated from wounded shoots of 17 of 20 inoculated seedlings and nonwounded shoots of 5 of 20 inoculated seedlings and was not cultured from control seedlings. To our knowledge, this is the first report of S. tsugae in Georgia and also the first demonstration of its ability to produce symptoms that have been attributed to it on any tree species. References: (1) M. Miller-Weeks and W. Ostrofsky. USDA. Forest Service. Online publication. NA-PR-01-10, 2010. (2) A. Y. Rossman et al. For. Pathol. 38:47. (3) D. R. Smith et al. For. Pathol. 33:141, 2003. (4) D. R. Smith and G. R. Stanosz. For. Pathol. 38:156, 2008